If you have a garden in Malawi... - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Horticulture in Malawi. PO Box 31131, Lilongwe 3, Malawi. Fax: +265 780 413 Email: GuenterBaumann GTZ@malawi.net